Public Debt as Private Liquidity - Woodford, Michael (American Economic Review, 1990)
From page 382– "I [the author] wish to argue that the analysis provided by the neoclassical model may not be an adequate guide to policy, even if certain of its predictions are correct. Instead, I [the author] direct attention to an alternative explanation of the effects of changes in the level of public debt, which leads to very different conclusions about the welfare consequences of such policies. According to this view, 'Ricardian equivalence' fails because of imperfect financial intermediation. Some economic units are liquidity constrained, which is to say that they are unable to borrow against their future income at a rate of interest as low as that at which the government borrows. Increased government borrowing can benefit such parties, insofar as they effectively receive a highly liquid asset, government debts, in exchange for giving the government an increased claim on their future income, their own claim to which represented a highly illiquid asset. A higher public debt, insofar as it implies a higher proportion of liquid assets in private sector wealth, increases the flexibility of the private sector in responding to variation in both income and spending opportunities, and so can increase economic efficiency."